2007
DOI: 10.1111/j.1755-0238.2007.tb00239.x
|View full text |Cite
|
Sign up to set email alerts
|

A functional association in Vitis vinifera L. cv. Cabernet Sauvignon between the extent of primary branching and the number of flowers formed per inflorescence

Abstract: The number of primary branches (those branches that arise directly from the rachis) and the total number of flowers were counted for inflorescences of Vitis vinifera L. cultivar Cabernet Sauvignon over a range of climates and a number of seasons as part of a yield prediction study. Regression analysis indicated that the number of primary branches per inflorescence exerted a strong control over the total number of flowers per inflorescence, with highly significant (P < 0.01) relationships explaining between 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
2
33
1
Order By: Relevance
“…Thus, the closer these volumes are, the more compact is the bunch (Sepahi 1980, Shavrukov et al 2004). Berry number depends on the number of flowers present in the inflorescence and on the proportion that sets successfully and is retained until harvest (Dunn and Martin 2007). According to our results, the number of berries per bunch plays a leading role in bunch compactness, having a positive relationship with this trait.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Thus, the closer these volumes are, the more compact is the bunch (Sepahi 1980, Shavrukov et al 2004). Berry number depends on the number of flowers present in the inflorescence and on the proportion that sets successfully and is retained until harvest (Dunn and Martin 2007). According to our results, the number of berries per bunch plays a leading role in bunch compactness, having a positive relationship with this trait.…”
Section: Discussionmentioning
confidence: 51%
“…Consequently, those morphoagronomic variables that were consistently retained in the analyses of the 2011, 2012 and 2013 data arise as the best set of predictors. Among them, the variables 1RmLe, BuLe and ToBeBu may be considered as primary and independent variables, whereas BuWe is a derived variable, and essentially arises from the number of berries of the bunch and its average mass (Dunn and Martin 2007). Moreover, they obtained high and similar absolute standardised coefficients in the discriminant functions over the years.…”
Section: Linear Discriminant Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…It has also been demonstrated that branching of IP continues after initiation until dormancy in season one (Pratt 1971, Srinivasan and Mullins 1981, Morrison 1991, where the degree of branching may be influenced by temperature during this period (Palma andJackson 1981, Dunn andMartin 2007). The research mentioned above, however, typically examines inflorescence structures as a whole, leaving a gap in the literature concerning the influence of temperature on outer arm development.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, regarding the number of clusters, there might be an influence on the next productive cycle number of flowers, as a result of the effects on the early stages of shoots inflorescence from the current cycle (Dunn and Martin, 2007).…”
Section: Discussionmentioning
confidence: 99%